The Recruitment Issues of Prospective Regional Head Candidates by Political Parties - junaidi junaidi junaidi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The mandate of Article 29 paragraph (2) of Law No.2/2008 requires that the recruitment of candidates for regional head/deputy regional head by political parties must be carried out in a democratic and open manner. However, the arrangement and implementation are left to each political party. This study analyzes the problem of recruitment of regional head candidates by political parties in a democratic and open manner which then provide ideas as alternative solutions. This research is normative legal research with a statute approach. The theory of democracy is used as a qualitative analysis guide and is presented descriptively. The results of this study conclude that the recruitment of prospective regional head/deputy regional head candidates, whose arrangements and implementation are left to political parties, tends to be carried out in an undemocratic and not open manner. Political parties tend to do so exclusively at the party elite level. Even though at the regional level a selection of prospective candidates was carried out by several political parties, the final decision was determined by the leadership at the central level. In addition, the pattern of recruitment is also very vulnerable to money politics. This is because political parties have full authority in recruiting prospective regional head candidates, so that they are not covered by The General Election Supervisory Agency (Bawaslu) and General Election Commissions (KPU) supervision. In the future, improvements need to be made so that arrangements regarding the recruitment of prospective regional head/deputy regional head candidates are strictly regulated in the Regional Head Election Law (Pilkada Law), not in the statutes of each political party.